Gut Microbial Metabolites on Host Immune Responses in Health and Disease - 윤종휘; 도준수; Velankanni Priyanka; 이충구; 권호근 (대한면역학회, 2023)
Intestinal microorganisms interact with various immune cells and are involved in gut homeostasis and immune regulation. Although many studies have discussed the roles of the microorganisms themselves, interest in the effector function of their metabolites is increasing. The metabolic processes of these molecules provide important clues to the existence and function of gut microbes. The interrelationship between metabolites and T lymphocytes in particular plays a significant role in adaptive immune functions. Our current review focuses on 3 groups of metabolites: short-chain fatty acids, bile acids metabolites, and polyamines. We collated the findings of several studies on the transformation and production of these metabolites by gut microbes and explained their immunological roles. Specifically, we summarized the reports on changes in mucosal immune homeostasis represented by the Tregs and Th17 cells balance. The relationship between specific metabolites and diseases was also analyzed through latest studies. Thus, this review highlights microbial metabolites as the hidden treasure having potential diagnostic markers and therapeutic targets through a comprehensive understanding of the gut-immune interaction.